Ceramic material and preparation method therefor - ZHANG RUI; LI CHUNGUANG; WEI SHENGNAN; GUO XIAOQIN; ZHAO XIN; CHEN LEIMING; FAN LEI; ZHANG XINYUE (2016)
The invention discloses a ceramic material and a preparation method therefor. The ceramic material is mainly prepared from the following raw materials in percentage by mass: 40% to 50% of red mud, 20% to 30% of bauxite, 5% to 10% of potash feldspar, 5% to 10% of kaolin and 5% to 10% of quartz sand. The ceramic material disclosed by the invention is prepared by taking the red mud as a main raw material and is high in hardness, good in density and low in production cost, so that the problems, i.e., environmental pollution and floor-occupied stacking caused by aluminum mineral industry are solved, industrial wastes can be sufficiently utilized, the waste is changed into the valuable, and the economic and environmental benefits are remarkable. 本发明公开了种陶瓷材料及其制备方法。该陶瓷材料主要由以下质量百分比的原料制成：赤泥40％～50％，铝矾土20％～30％，钾长石5％～10％，高岭土5％～10％，石英砂5％～10％。本发明的陶瓷材料以赤泥为主要原料制成，所得陶瓷材料硬度高，致密度好，生产成本低，不仅解决了铝矿业带来的环境污染、占地堆放问题，又能充分利用工业废料，变废为宝，经济效益和环保效益显著。